Chlorine-Functional Silsesquioxanes (POSS-Cl) as Effective Flame Retardants and Reinforcing Additives for Rigid Polyurethane Foams - Anna Strąkowska; Sylwia Członka; Karolina Miedzińska; Krzysztof Strzelec (Molecules, 2021)
The subject of the research was the production of silsesquioxane modified rigid polyurethane (PUR) foams (POSS-Cl) with chlorine functional groups (chlorobenzyl, chloropropyl, chlorobenzylethyl) characterized by reduced flammability. The foams were prepared in a one-step additive polymerization reaction of isocyanates with polyols, and the POSS modifier was added to the reaction system in an amount of 2 wt.% polyol. The influence of POSS was analyzed by performing a series of tests, such as determination of the kinetics of foam growth, determination of apparent density, and structure analysis. Compressive strength, three-point bending strength, hardness, and shape stability at reduced and elevated temperatures were tested, and the hydrophobicity of the surface was determined. The most important measurement was the determination of the thermal stability (TGA) and the flammability of the modified systems using a cone calorimeter. The obtained results, after comparing with the results for unmodified foam, showed a large influence of POSS modifiers on the functional properties, especially thermal and fire-retardant, of the obtained PUR-POSS-Cl systems.